2021
DOI: 10.1016/j.joule.2021.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer rates and electron trapping at buried interfaces of perovskite solar cells

Abstract: Dominating loss mechanisms were identified at hole-selective buried interfaces engineered with carbazole-based self-assembled monolayers between a metal halide perovskite absorber and a conductive metal oxide. The analysis of surface photovoltage transients with a minimalistic kinetic model allowed for the extraction of interfacial electron trap densities and hole transfer rates and their correlation with open-circuit voltages and fill factors of the corresponding highefficiency solar cells is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
210
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(223 citation statements)
references
References 57 publications
12
210
1
Order By: Relevance
“…We found that tailoring the dimensionality (n) of the 2D perovskite fragments at the electron-selective interface of inverted PSCs is essential to enable efficient top-contact passivation through 2D perovskite passivation layers. This interface has frequently been ignored because it is assumed that the conventional electron-selective layer, C 60 (or its derivatives), provides sufficient passivation of 3D perovskites (21); instead, attention has predominantly focused on the hole-selective interface of inverted PSCs, situated at the (transparent) bottom contact of the device (22)(23)(24)(25). However, recent reports have revealed that C 60 is only weakly bonded to perovskite layers, which induces a high energetic disorder between perovskite and C 60 layers that limits device performance at elevated operating temperatures (5,6,26).…”
mentioning
confidence: 99%
“…We found that tailoring the dimensionality (n) of the 2D perovskite fragments at the electron-selective interface of inverted PSCs is essential to enable efficient top-contact passivation through 2D perovskite passivation layers. This interface has frequently been ignored because it is assumed that the conventional electron-selective layer, C 60 (or its derivatives), provides sufficient passivation of 3D perovskites (21); instead, attention has predominantly focused on the hole-selective interface of inverted PSCs, situated at the (transparent) bottom contact of the device (22)(23)(24)(25). However, recent reports have revealed that C 60 is only weakly bonded to perovskite layers, which induces a high energetic disorder between perovskite and C 60 layers that limits device performance at elevated operating temperatures (5,6,26).…”
mentioning
confidence: 99%
“…Instead, various observable quantities are measured as a function of time after photoexcitation, which are more or less closely related to the charge-carrier concentration. These measurable quantities include voltage, [1][2][3] luminescence, [4,5] conductivity [6][7][8] and the amount of free carrier absorption. [9,10] Sometimes, extracted currents in response to a laser pulse are measured as a (relatively) direct assay of charge carriers being extracted as a function of time.…”
mentioning
confidence: 99%
“…According to the redox reaction between the interface of NiO x or NiO x ‐IL HTL and perovskite layer, the amount of Ni 3+ in HTL decreases and the amount of Ni 2+ increases during the reaction process. Therefore, we used lift‐off method (Figure 4g, the details are described in Supporting Information) to concretely study the content changes of Ni 3+ and Ni 2+ in NiO x and NiO x ‐IL buried films after the interfacial reaction for long‐term actual operation (above operational stability measurements: one sun, ambient air, MPP tracking, 1000 h) [59, 61] . As shown in Figure 4h, it is calculated that the ratio of Ni 3+ /Ni 2+ in the control NiO x film decreases from 1.35 to 0.77, while the Ni 3+ /Ni 2+ ratio of NiO x ‐IL film decreases slightly from 1.92 to 1.71.…”
Section: Resultsmentioning
confidence: 99%